Experimental research and mechanism analysis of combined gravity-magnetic separation on coal gasification fine slag - Panpan Fan; Zengqiang Ge; Zhenyang Ren; Weiren Bao; Jiancheng Wang; Lianping Dong; Minqiang Fan (International Journal of Coal Science & Technology)
Abstract Coal gasification fine slag (CGFS) is a solid waste produced in the process of coal gasification. The separation of residue carbon in CGFS is essential for its resource utilization. In this study, the basic physical properties of CGFS were analyzed and the effect of physical separation experiments were carried out. The gravity separation results indicated that the coarser particle size fraction achieved a good separation effect. The High-carbon product has a yield of 12.53% with an ash content of 16.84%, and the High-ash product has a yield of 17.85% with an ash content of 98.15% were obtained. Theoretical calculations indicated that the apparent density difference between residue carbon and ash minerals in the water phase environment was the basis for achieving separation. The Rich-ash product was further separated by magnetic separation, and both magnetic field characteristics, water elutriation frequency and grinding time had impacts on the magnetic separation effect. Compared to gravity separation alone, the combined gravity-magnetic separation further enhanced the separation effect of residue carbon and ash minerals. The ash content of the Rich-ash product decreased from 80.56% to 69.52% due to the removal of high-ash Fe oxides, and the yield of combined separation tailings increased from 17.85% to 41.75%. The characterization results obtained through SEM-EDS, VSM, XRD and XRF analysis demonstrated significant differences in saturation magnetization, mineral composition and peak intensity among magnetic separation products, confirming that the feasibility of magnetic separation. The research findings contribute to a better understanding of the separation mechanism and provide a new separation process for efficiently enriching residue carbon from CGFS, also facilitate the step utilization of separation products.